Learning in Networks During the Covid-19 Pandemic - Chrisnaji Banindra Yudha; Zulela Zulela; Trisni Handayani (Jurnal Basicedu, 2021)
In the period of Pandemic Novel Corona Virus Disease 2019 (Covid-19) several online learning models are applied to the educational world. This study aims to determine 1) student responses easy to access integration of WAG learning media and Zoom Application 2) understanding of material in learning using a combination of WAG learning media and Zoom Application, 3) the effectiveness of the combination of WAG learning media and Zoom Application in online learning. The method used in this study is a descriptive qualitative research method through survey techniques. The research instrument used was in the form of questionnaires and online interviews given to 375 Elementary School Teacher Education Study Program students (PGSD). The results of the study showed that as many as 71,14% of students agreed in the ease of access to the combination of WAG learning media and Zoom Application, as many as 71,25% of students agreed in understanding the material in learning by using a combination of WAG learning media and Zoom Application, as many as 72% of students agreed on the integration WAG learning media and Zoom Application in effective online learning. It can be concluded that the combination of WAG and zoom applications in online learning was received by students, this was seen by students' responses through the instruments that were delivered and agreed.